2021
DOI: 10.1186/s13059-021-02337-8
|View full text |Cite
|
Sign up to set email alerts
|

Best practices on the differential expression analysis of multi-species RNA-seq

Abstract: Advances in transcriptome sequencing allow for simultaneous interrogation of differentially expressed genes from multiple species originating from a single RNA sample, termed dual or multi-species transcriptomics. Compared to single-species differential expression analysis, the design of multi-species differential expression experiments must account for the relative abundances of each organism of interest within the sample, often requiring enrichment methods and yielding differences in total read counts across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 153 publications
0
38
0
Order By: Relevance
“…There are various approaches to define the background of an RNA-seq dataset [ 32 ]. The effect of different filtering methods on differential expression results has been investigated [ 33 ], and provides us with some practical recommendations to avoid sampling biases described by Timmons et al [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are various approaches to define the background of an RNA-seq dataset [ 32 ]. The effect of different filtering methods on differential expression results has been investigated [ 33 ], and provides us with some practical recommendations to avoid sampling biases described by Timmons et al [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, methods such as RNA-seq, comparative microarray, next-generation sequencing (NGS), and cDNA suppression subtracted hybridization (SSH) are appropriate for studying the whole transcriptome of pathogenic mycobacterial species. Recently, RNA-seq gene expression studies have shown the ability to capture pictures of the differential expression of transcripts seen in mycobacterium species ( Chung et al., 2021 ). Previous research revealed a new transcriptomic method that used overlapping of chromatin immunoprecipitation sequencing (ChIP-seq) RNAP (RNA Polymerase), and NusA RNA-Seq data to detect sRNA expression in Mtb .…”
Section: Multi-omics Approaches To Study Mycobacterial Diseasesmentioning
confidence: 99%
“…High-throughput sequencing technologies have been used to explore complex biological and physiological processes of microbes. Transcriptomic analysis based on RNA sequencing is a reliable approach to profile genes that are expressed differently and for understanding the gene network [ 32 ]. Therefore, transcriptomics can provide a system-wide understanding of the complex biological processes of fungi.…”
Section: Introductionmentioning
confidence: 99%